Testing the validity of Fama French Five Factor Asset Pricing Model: Evidence from Turkey - Feyyaz Zeren; Tayfun Yilmaz; Murat Belke (Financial Studies, 2019)
Fama and French introduced a five - Factor Asset Pricing Model (FF5), adding a new perspective to asset pricing models in the literature in 2015. The aim o f this paper is to investigate the validity of Fama French (2015) Five Factor Asset Pricing Model for 18 c ompanies whose shares are listed in Istanbul Stock Market Sustainability Index. According to obtained findings, the coefficient of the profitability f actor, from the new variables added to the three - factor model to build the FF5 asset pricing model, was po sitive and statistically significant, whereas the coefficient of investment factor was not statistically significant. As a result of the study coverin g 1995Q1 - 2017Q3 period, there was not enough evidence that the FF5 Model was valid for Istanbul Stock Mark et Sustainability Index. In this context, the model will not be beneficial for investors in the estimation of the returns of the companies in the Istanbul Stock Market Sustainability Index.
Keywords: C23; G12; 330; Fama French; Five-Factor Model; Asset Pricing; Istanbul Stock Market Sustainability Index